“I Did Not Know Then...” Two Autothematic Poems - Pasterski, Janusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The author discusses the autothematic motifs in the poems „Sitowie” by Julian Tuwim and „Przeciwne wiatry” by Tomasz Różycki. The author analyses both poems and compares the transformations of the autothematic motifs, emphasizing the connections with literary tradition and the dialogue of the poets’ artistic attitudes. In both literary works the key problem is the relation between words and things.
Translated by Edyta Więcławska.
Keywords: poetry; autothematic motifs; Julian Tuwim; Tomasz Różycki